Routledge handbook of religion and politics [ - Haynes, Jeffrey (Routledge international handbooks, 2009)
From the United States to the Middle East, Asia and Africa, religion has become an increasingly important factor in political activity and organisation. This handbook provides a global survey of the interaction of religion and politics